1992
DOI: 10.1002/ana.410320306
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II receptor binding associated with nigrostriatal dopaminergic neurons in human basal ganglia

Abstract: In the human brain, receptor binding sites for angiotensin are found in the striatum and in the substantia nigra pars compacta overlying dopamine-containing cell bodies. In contrast, angiotensin-converting enzyme occurs in the substantia nigra pars reticulata and is enriched in the striosomes of the striatum. In this study, using quantitative in vitro autoradiography, we demonstrate decreased angiotensin receptor binding in the substantia nigra and striatum of postmortem brains from patients with Parkinson's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 24 publications
0
55
0
2
Order By: Relevance
“…The brain possesses a local angiotensin system (Gendron et al, 2003;McKinley et al, 2003;Pan, 2004;Rodriguez-Pallares et al, 2004), and the results of previous studies have suggested that AII and its receptors play an important role in modulating striatal dopamine (DA) levels. Both AII and AII receptors as well as angiotensinogen and angiotensin-converting enzyme (ACE) have been observed in the striatum (Quinlan and Phillips, 1981;Brownfield et al, 1982;Chai et al, 1987;Allen et al, 1992Allen et al, , 1998, and AII stimulates the release of newly synthesized DA via angiotensin type 1 receptors (AT 1 ) located in the striatal DA terminals (Mendelsohn et al, 1993;Brown et al, 1996;Ge and Barnes 1996). However, it has recently been shown that in several cell types, including neurons, reactive oxygen species (ROS) play a crucial role in the signaling of AII via AT 1 receptors.…”
mentioning
confidence: 99%
“…The brain possesses a local angiotensin system (Gendron et al, 2003;McKinley et al, 2003;Pan, 2004;Rodriguez-Pallares et al, 2004), and the results of previous studies have suggested that AII and its receptors play an important role in modulating striatal dopamine (DA) levels. Both AII and AII receptors as well as angiotensinogen and angiotensin-converting enzyme (ACE) have been observed in the striatum (Quinlan and Phillips, 1981;Brownfield et al, 1982;Chai et al, 1987;Allen et al, 1992Allen et al, , 1998, and AII stimulates the release of newly synthesized DA via angiotensin type 1 receptors (AT 1 ) located in the striatal DA terminals (Mendelsohn et al, 1993;Brown et al, 1996;Ge and Barnes 1996). However, it has recently been shown that in several cell types, including neurons, reactive oxygen species (ROS) play a crucial role in the signaling of AII via AT 1 receptors.…”
mentioning
confidence: 99%
“…A fuller account of Ang II receptors in the human brain has been published [48][49][50]. The high density of Ang II receptors in the substantia nigra occurs over pigmented, presumably dopaminergic, neurons [51]. The binding in this site, and in the striatum, is not observed in any of the other species we have studied.…”
Section: Ang II Receptors and Function During Pregnancymentioning
confidence: 84%
“…Both ACE and angiotensin receptors were identified in dopaminergic neurons of basal ganglia (Allen et al, 1992). Significant decreased dopamine release determined by ACE inhibitors was also demonstrated (Obata et al, 2008).…”
Section: Introductionmentioning
confidence: 92%